PUBLIC TRANSPORTATION THROUGH THE CLUSTERING ANALYSIS OF BUS STOPS. CASE STUDY MANIZALES, COLOMBIA - Jorge Alberto MONTOYA; Diego Alexander ESCOBAR; Carlos Alberto MONCADA (Geo Journal of Tourism and Geosites)
The objective of this research is to identify the main characteristics and geographical distribution of bus stops, associated with collective public transport systems, through data analysis techniques that can identify clustering patterns based on various characteristics of the stops, such as geographical location, passenger flow, service demand, land use, etc. number of routes available, slope of the road, signage, among other relevant factors. The main result of this study is that t he current layout of the stops is distributed according to the main characteristics of their environment, allowing us to conclude that the grouping of transport stops facilitates the interpretation of the location and operability of the stops, thus allowi ng to improve decision-making in the implementation of stops, guaranteeing an adequate operation of the service without compromising coverage and travel time of users.